An asset management approach to optimize water meter replacement. (June 2018) - Yazdandoost, Farhad; Izadi, Ardalan
Abstract: Despite existence of many developed approaches for identifying optimal time of Water Meters (WMs) replacement, less attention has been paid to the impact of WM failure risk on utilities revenues and the proper time of replacement. Here, the Asset Management (AM) approach is introduced as a holistic managing framework optimizing Life Cycle Costs (LCC), especially incorporating WM failure risk in asset replacement decisions. The proposed AM framework is based on four core steps. The application of the proposed framework for a real case study has shown confidence in finding the economical time of WM replacement. It was further shown that the risk costs associated with WM failure have higher impacts on optimal time of WM replacement than the revenue lost due to its inaccuracy. The sensitivity analyses of input data values show that water price, initial investment and accuracy degradation rate have the highest impacts on LCCs amongst other parameters. Highlights: The Asset Management (AM) approach to water meter management presented. A comprehensive AM framework for optimal replacement of water meters described. The framework integrates failure risks into optimal replacement decisions. Impact of failure risks on optimal replacement of water meters is non-negligible.